CITIZENS’TRUST IN PUBLIC AUTHORITIES OF LATVIA AND PARTICIPATION PARADIGM - Seimuskane, Lilita; Vorslava, Maija (European Scientific Journal, ESJ, 2014)
Lack of trust in public authorities is a problem not only in Latvia. The trend of decreasing citizens’ trust can be observed all over the world. However, Latvian government and the parliament enjoy an extremely low level of trust. According to the Eurobarometer 79202 data of Spring 2013, only 15 % of respondents tend to trust in the parliament of Latvia, and 20 % of respondents have tend to trust in national government. The gap between the society and political power has grown considerably. The majority of electors are neither satisfied with the democracy form of the parties, nor do they approve of their activities in the state and local governments. At the same time citizens’ trust in local governments is much higher than in the national government and parliament, namely, 42% of residents trust in local public authorities. This article deals with the theoretical aspects of public trust, as well as, on the basis of survey, analyzes public opinion about various public authorities in Latvia. This publication aims to explore whether there is any coherence between the levels of trust that the public expresses in various public institutions? Whether citizens’ positive assessment of the performance of local authorities has positive impact on evaluation of the national parliament and government? Whether in local authorities where citizens are more satisfied with local authorities’ work, the citizen participation is also higher?